Addressing the challenges to increase the efficiency of translating nanomedicine formulations to patients. (4th March 2021) - Bhattacharjee, Sourav; Brayden, David J.
ABSTRACT: Introduction: Nanotechnology is in a growth phase for drug delivery and medical imaging. Nanomaterials with unique properties present opportunities for encapsulation of therapeutics and imaging agents, along with conjugation to ligands for targeting. Favorable chemistry of nanomaterials can create formulations that address critical challenges for therapeutics, such as insolubility and a low capacity to cross the blood-brain-barrier (BBB) and intestinal wall. Areas covered: The authors investigate challenges faced during translation of nanomedicines while suggesting reasons as to why some nanoformulations have under-performed in clinical trials. They assess physiological barriers such as the BBB and gut mucus that nanomedicines must overcome to deliver cargos. They also provide an overview with examples of how nanomedicines can be designed to improve localization and site-specific delivery (e.g., encapsulation, bioconjugation, and triggered-release). Expert opinion: There are examples where nanomedicines have demonstrated improved efficacy of payload in humans; however, most of the advantages conferred were in improved pharmacokinetics and reduced toxicity. Problematic data show susceptibility of nanoformulations against natural protective mechanisms present in the body, including distribution impediment by physiological barriers and activation of the reticuloendothelial system. Further initiatives should address current challenges while expanding the scope of nanomedicine into advanced biomedical imaging and antibiotic delivery.